The Influence of Project-Based Learning Model on Visual Communication Design Learning Outcomes of Students at State Vocational School 1 Kotamobagu - Harry Septian Laute; Harrychoon Angmalisang; Hiskia Kamang Manggopa; Parabelem Tinno Dolf Rompas (JR Education, 2026)
This study aims to determine the effect of implementing the Project-Based Learning (PjBL) model using the Kodular application on the creativity and learning outcomes of 11th-grade DKV 1 students in the Fundamentals of Visual Communication Design subject at SMKN 1 Kotamobagu. This study used a quantitative approach with a quasi-experimental design involving two groups: a control class and an experimental class, each with 20 students (a total of 40 students). The research instrument was tested for validity and reliability, with all items declared valid (r count 0.338–0.794 > 0.312) and reliable (Cronbach's Alpha 0.917). The descriptive analysis results showed an increase in the average pretest and posttest scores in the experimental class from 42.5 to 83.5, while in the control class, the score increased from 41 to 80.5. The normality test showed that the data were normally distributed (Sig. 0.227 and 0.731), while the homogeneity test showed that both groups had homogeneous variances (Sig. 0.214 and 0.331). The t-test indicated a significant effect of the Project-Based Learning (PjBL) model on learning outcomes, with a sig. 0.000 and a calculated t of 9.811. The F-test yielded an F-value of 96.259 with a significance level of 0.000, indicating that the model simultaneously influenced learning outcomes. The determination test obtained an R-square value of 0.717, indicating that the model explained 71.7% of the variation in learning outcomes. This study concludes that the implementation of Project-Based Learning (PjBL) using Kodular effectively improves student creativity, learning motivation, and learning outcomes in the Visual Communication Design subject.